2019
DOI: 10.1536/ihj.18-632
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Catecholamines in the Plasma of Patients with Cardiopulmonary Arrest

Abstract: So far, there remains a controversy regarding the efficacy of epinephrine (Ep) in patients with cardiopulmonary arrest (CPA). In this study, we evaluated the importance of the plasma levels of catecholamines prior to the administration of Ep in patients with CPA. Patients with out-of-hospital cardiac arrest (OHCA) who were transferred to Gunma University Hospital were enrolled prospectively between July 2014 and July 2017. The levels of catecholamines [Ep, norepinephrine (NEp), and dopamine] and vasopressin (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…In the ROSC (+) group, the dosages of Ep and resuscitation time after arrival at the hospital were significantly lower and shorter, respectively. These results coincide with the findings of our previous report [ 12 ]. This suggests that the levels of endogenous Ep and Nep in the plasma before the administration of Ep are markedly increased in patients with OHCA, and those levels may not be related to the length of resuscitation time and the frequency of defibrillation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the ROSC (+) group, the dosages of Ep and resuscitation time after arrival at the hospital were significantly lower and shorter, respectively. These results coincide with the findings of our previous report [ 12 ]. This suggests that the levels of endogenous Ep and Nep in the plasma before the administration of Ep are markedly increased in patients with OHCA, and those levels may not be related to the length of resuscitation time and the frequency of defibrillation.…”
Section: Discussionsupporting
confidence: 94%
“…Successful resuscitation, that is, ROSC (+), was defined as detection of a pulse at the carotid artery, femoral artery, or radial artery under advanced CPR and subsequent maintenance of systolic pressure ≥80 mmHg for 1 h with or without the continuous administration of vasoconstrictive agents intravenously or intraosseously [ 12 ]. Patients not achieving the above criteria were defined as ROSC (−).…”
Section: Methodsmentioning
confidence: 99%
“…However, the Japanese FDMA advises all medical-control authorities to prescribe CPR instruction protocols based on uniform DA recommendations. 15) Third, prior/concomitant medical history and estimated diagnosis as well as information about hospital care 36,37) after transfer to the emergency department of hospitals among OHCA patients were not included in the All-Japan Utstein registry of FDMA. Fourth, there might be unrecognized confounding factors affecting the association between bystander CPR implementation with or without DA, location of arrest, and survival outcome after OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…Successful resuscitation, ROSC (+), was defined as detection of a pulse at the carotid artery, femoral artery, or radial artery under advanced CPR, and subsequent maintenance of systolic pressure ≥80 mmHg for 1 h with or without continuous administration of vasoconstrictive agents intravenously or intra-osseously [ 12 ]. Patients not achieving the above criteria were defined as ROSC (−).…”
Section: Methodsmentioning
confidence: 99%
“…evaluated the plasma Ep levels in patients with OHCA and showed that, prior to the administration of Ep, they were significantly lower in resuscitated patients than non-resuscitated patients [ 11 ]. In addition, we previously reported that the plasma Ep levels prior to the administration of Ep were significantly lower in the ROSC (+) group than the ROSC (−) group in patients with cardiogenic CPA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%